The Influence of Language Attitudes on Language Choice among Mandarin Education Students at UNESA - Siska Pratiwi; Kaesyanandra Syifa Frilyrizatna Pangestuti; Maria Mintowati; Rokhishotul Amaliyah (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2026)
This study explores how language attitudes relate to language choice among 34 Mandarin Education students at Universitas Negeri Surabaya (UNESA) batch 2025. Using a mixed-method approach, data were collected through an online questionnaire and analyzed through descriptive statistics, simple linear regression, and thematic analysis. The findings reveal that students generally perceive Mandarin positively and recognize its value in academic and professional contexts. However, the regression analysis indicates that the influence of language attitudes on language choice was positive but statistically insignificant (R² = 0.094; p = 0.078). The qualitative findings indicate that Mandarin use is shaped by students’ confidence, opportunities for practice, learning environment, and language difficulties, particularly in vocabulary, tones, and pronunciation. This study highlights that Mandarin learning should move beyond building positive perceptions by providing supportive communication environments and practical speaking activities to encourage active language use.